2004
DOI: 10.1021/ic0347945
|View full text |Cite
|
Sign up to set email alerts
|

NO Binding to Cobalamin:  Influence of the Metal Oxidation State

Abstract: Density functional and molecular orbital theory calculations on models for cobalamin suggest that NO binds similarly to the Co(II) and Co(III) oxidation states. However, Co(III) can bind water far more strongly than Co(II) as a sixth ligand, so that the competition between water and NO complexation strongly favors water for Co(III) in the gas phase. Although the Co(II) oxidation state is found to bind water slightly more strongly than NO in the gas phase, the inclusion of solvation effects via the polarizeable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 35 publications
3
26
0
Order By: Relevance
“…[13,14] The oxidation state of the Co center of NOCbl is also of considerable interest. [11,12,[15][16][17] Herein, we report the synthesis and X-ray structural characterization of NOCbl, which was prepared by reacting hydroxycobalamin hydrochloride with the NO donor 2-(N,Ndiethylamino)diazenolate-2-oxide (DEA-NONOate) under strictly anaerobic, alkaline conditions (pH 8.9).…”
mentioning
confidence: 99%
“…[13,14] The oxidation state of the Co center of NOCbl is also of considerable interest. [11,12,[15][16][17] Herein, we report the synthesis and X-ray structural characterization of NOCbl, which was prepared by reacting hydroxycobalamin hydrochloride with the NO donor 2-(N,Ndiethylamino)diazenolate-2-oxide (DEA-NONOate) under strictly anaerobic, alkaline conditions (pH 8.9).…”
mentioning
confidence: 99%
“…4 shows the calculated (UB3LYP) spin densities for 5, 6 ‡ , and 7. We use both spin densities and atomic charges, because the latter have been shown [32] not to reveal electron transfer in transition-metal complexes, whereas the calculated spin density gives a detailed and accurate picture of the electronic features of reactants, transition states and products. Table 6 shows the calculated NBO [33,34] charges for the species described above.…”
Section: The Sncl 2 -Catalysed Rearrangement Solvated By Methanolmentioning
confidence: 99%
“…[74] Experimental and theoretical work from our laboratory proved that Cbl(H 2 O) does not react with NO at pH 7. [75,76] Nevertheless, it was reported later that Cbl(H 2 O) reacts with NO at low pH, under conditions in which the dimethylbenzimidazole group is protonated and subsequently dechelates. [77] The final product of this reaction was not a Co III -(NO) complex but Co II -(NO), or better described as Co III -(NO -).…”
Section: Reductive Nitrosylation Of Water-soluble Cobalt Porphyrinsmentioning
confidence: 99%
“…As mentioned in the previous section, aquacobalamin, [Cbl(H 2 O)], does not react with NO at pH 7, [75,76] nevertheless, it was reported that it can undergo reductive nitrosylation at low pH to generate a Co III -NO -complex or Cbl(NO -) [77] in a manner similar to that of Co porphyrins. [79] As a natural extension of the kinetic and mechanistic studies on Co porphyrins, [80] the reductive nitrosylation of Cbl(H 2 O) at low pH was revisited.…”
Section: Reductive Nitrosylation Of Aquacobalamin At Low Phmentioning
confidence: 99%
See 1 more Smart Citation